AB0438 Efficacy and Safety of Tabalumab, an Anti-B Cell Activating Factor Monoclonal Antibody, in Patients with Rheumatoid Arthritis WHO HAD an Inadequate Response to Tnf-Alpha Inhibitors: Results from A Phase 3 Multicenter, Randomized, Double-Blind Study. (10th June 2014) - Schiff, M.; Combe, B.; Dörner, T.; Kremer, J.M.; Huizinga, T.W.; Veenhuizen, M.; Gill, A.; Zou, H.; Komocsar, W.; Berclaz, P.-Y.; Ortmann, R.; Lee, C.
Abstract : Background: Tabalumab is a monoclonal antibody that neutralizes membrane-bound and soluble B cell activating factor (BAFF). Objectives: Evaluate efficacy and safety of tabalumab, in RA pts who had an inadequate response to ≥1 TNF-a inhibitors, in a randomized, double-blinded, placebo-controlled study. Methods: 456 pts with active RA were enrolled in this 24-wk study evaluating 2 different subcutaneous (SQ) tabalumab doses (120mg every 4 wks [120/Q4W] or 90mg every 2 wks [90/Q2W]) vs placebo (PBO). At wk 0, pts received a SQ loading dose that was 2 times the planned treatment dose (ie, 240mg, 180mg, or PBO). Eligible pts included those receiving background DMARDs and having previously discontinued TNF-a inhibitor therapy due to lack of efficacy or intolerance. The primary efficacy endpoint was ACR20 at 24 wks; secondary efficacy endpoints included ACR50, change in DAS28-CRP and change in HAQ-DI at 24 wks. This study was terminated early due to futility. Results: At baseline, the study population was mostly female (83.6%) and seropositive (RF and/or anti-CCP, 92%), with a mean age of 53.2 yrs, mean RA diagnosis of 8.2 yrs, and moderate to high disease activity DAS28-CRP of 5.9±1.0 (mean ± SD). At wk 24, there were no significant differences among the 120/Q4W, 90/Q2W, and PBO groups in the percentage of pts who achieved ACR20 (NRI; 17.6%, 24.3%, 20.0%) and ACR50 (NRI; 7.2%, 5.4%, 3.9%), and no significant differences in DAS28-CRP (mBOCF; 5.1±1.5, 5.1±1.5, 5.2±1.4; mean ± SD), or HAQ-DI (mBOCF; 1.5±0.7, 1.6±0.7, 1.6±0.7; mean ± SD). After 24 wks, changes in CD3-CD20+ B cells in the 120/Q4W, 90/Q2W, and PBO groups were generally consistent with prior phase 2 results (−10.8%, −9.6%, and 10.9%), as were changes in immunoglobulin levels: IgM (−15.0%, −14.8%, 0.2%), IgA (−9.0%, −9.0%, 1.6%), and IgG (−7.2%, −7.9%, 1.4%). Safety was evaluated in all randomized pts who received ≥1 dose of study treatment (n=454). Discontinuations due to an AE were similar across the 120/Q4W, 90/Q2W, and PBO groups (2.6%, 2.7%, 2.6%) as were TEAEs (59.5%, 51.7%, 51.9%) and SAEs (4.6%, 4.1%, 3.9%). For the 120/Q4W, 90/Q2W, and PBO groups, AEs of interest were infections (24%, 26%, 23%); injection-site reactions (2.6%, 4.8%, 0.0%); and allergic/hypersensitivity events (3.9%, 4.1%, 3.9%). There were no differences between groups in reports of opportunistic infections, tuberculosis, or serious infection events. No deaths occurred. Conclusions: In this phase 3 study, tabalumab demonstrated no clinical efficacy despite evidence of biologic activity, suggesting that targeting BAFF may not be a viable therapeutic approach to treating pts with RA. There were no differences in reports of infection or allergic/hypersensitivity events and no new or unexpected safety findings for RA pts receiving tabalumab. Disclosure of Interest: M. Schiff Consultant for: Eli Lilly and Company, B. Combe Grant/research support: Pfizer, Roche-Chugai, Speakers bureau: Eli Lilly and Company, BMS, Merck, Pfizer, Roche-Chugai, UCB, T. Dörner Grant/research support: Roche-Chugai, Sanofi-Aventis, Janssen, UCB, Consultant for: Eli Lilly and Company, Roche-Chugai, UCB, Speakers bureau: Roche-Chugai, UCB, J. Kremer Grant/research support: Eli Lilly and Company, Consultant for: Eli Lilly and Company, T. Huizinga Consultant for: Eli Lilly and Company, M. Veenhuizen Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, A. Gill Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, H. Zou: None declared, W. Komocsar Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P.-Y. Berclaz Employee of: Eli Lilly and Company, R. Ortmann Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C. Lee Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company DOI: 10.1136/annrheumdis-2014-eular.3305